The FeSTivaLS trial protocol: A randomized evaluation of the efficacy of functional strength training on enhancing walking and upper limb function later post stroke. Issue 5 (18th April 2012) - Mares, Kathryn; Cross, Jane; Clark, Allan; Barton, Garry R.; Poland, Fiona; O'Driscoll, Marie‐Luce; Watson, Martin J.; McGlashan, Kate; Myint, Phyo K.; Pomeroy, Valerie M.
<x xml:space="preserve">Abstract</x> Rationale Functional Strength Training may enhance motor function of people who are more than six months post stroke. Aims to evaluate the clinical efficacy of enhancing upper and lower limb motor function with FST to explore participants' views (expectations and experiences) of FST, and to determine what cost‐effectiveness data to collect in a subsequent Phase III trial. Design Randomized, observer‐blind trial with embedded qualitative investigation of participants' views of FST (n = 6, purposive sampling). Study Participants (n = 58), six months to five years after stroke with difficulty using their paretic upper (UL) and lower limbs (LL) for everyday functional activity. All will be randomized to either FST‐UL or FST‐LL delivered in their own homes for fours days each week for six weeks. FST involves repetitive progressive resisted exercise during goal directed functional activities. The therapist's main input is to provide verbal prompting and feedback. Outcomes Measures will be undertaken before randomization (baseline), after the six‐week intervention (outcome) and six weeks thereafter (follow‐up). Primary outcomes for clinical efficacy will be the Functional Ambulation Categories (FAC) and the Action Research Arm Test (ARAT). Clinical efficacy analysis will use the proportional odds model for FAC and a Mann‐Whitney test for ARAT. Participants' views of FST will be explored at baseline and outcome through audiotaped, semi‐structured, narrative approach, interviews. The analytic process for interviews will sort transcribed data thematically and seek categories to inform conceptualization (theory‐building). A purpose‐designed cost questionnaire will identify what cost resource items are likely to be affected by FST.